Abu Nu‛aym Al-Iṣfahānī (d. 430/1038): His Professional Life - Meis Al-Kaisi (Jurnal Theologia, 2022)
Abu Nu‛aym al-Iṣfahānī (d. 430/1038), a celebrated scholar and author of many works, famed for his Ḥilya, and mostly remembered as a Sufi advocate, historiographer, and hadith traditionist. Despite his renowned reputation, one struggles to find much research concerning his life and works. Classical Arabic literature presents some information about him in scattered short biographical entries. Modern scholarship has even less to offer in this regard. None of the existent sources presents a biography that delivers a precise examination of Abu Nu‛aym’s life, journeys, teachers, students and works, all in one place. This paper is a sequel to my previously published piece entitled “Abu Nu‛aym al-Iṣfahānī (d. 430/1038): Conflicting Opinions” which evaluates the opinions of Abu Nu‛aym’s supporters and critics. Published by “Teosofia” in December 2021, the article examines the praise Abu Nu‛aym had received from his proponents as well as the criticism from his opponents. In this current paper the focus is on Abu Nu‛aym’s professional life. It includes lists of all his teachers, students, and works, along a detailed presentation of which of Abu Nu‛aym’s works have been published, which survived in only manuscript form and which are considered lost. This paper is meant to complement the previous one and together present a concise biography that treats all the details of Abu Nu‛aym’s life. This paper is the result of many years of search for information about Abu Nu‛aym in primarily classical sources, but also modern literature, as well manuscript and library catalogues for details on the available manuscript copies and printed editions of his works.